DEVELOPING A DATA-DRIVEN METHOD FOR YACHT DIMENSION PREDICTION - Hassan, Md. Tawhid; Khan, Md. Riad (Department of Marine Engineering, Universitas Hang Tuah, 2026)
A yacht's principal dimensions can be found in many ways. However, due to the massive technological advancements in the yacht industry, using these ancient methods is just a waste of time. A new statistical method is necessary to determine yacht dimensions in an easy and effective way. In this paper, 122 modern yacht data have been used to investigate the relationship between length, breadth, draught, speed, gross tonnage, and power, and to perform regression analysis to develop a new method for estimating yacht dimensions. This study developed two predictive models: Model 1 utilizes empirical ratios and trendline equations, while Model 2 employs sequential stepwise multiple regression. The models effectively estimate breadth, draft, gross tonnage (GT), speed, and power from a specified length, with geometric parameters (e.g., GT prediction R²=0.97 in Model 1) showing higher reliability than performance parameters. The minimum and maximum ratio of Length to Breadth, draught to breadth, for a different range of ship length is also determined. This research is conducted in such a way that the owner’s requirement for a new yacht is the length, and other particulars are determined accordingly.